2021
DOI: 10.1007/s00431-021-04025-y
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa infection in respiratory samples in children with neurodisability—to treat or not to treat?

Abstract: The objective was to investigate the prevalence of Pseudomonas aeruginosa (PA) in patients with complex neurodisability and current treatment practice in our centre in order to inform future guidelines. A retrospective case note review was undertaken at a tertiary children’s hospital. One hundred sixty-two patients (mean age 11.7 years) with a primary diagnosis of neuromuscular disease (NMD) or severe cerebral palsy (CP) and a respiratory sample sent for analysis during the study period were studied. Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Our key findings are that Pa colonisation is frequent in adults on LTV, affecting nearly 1 in 5 (17.6%). Consistent with previous data [ 7 ], we found that tracheostomy is a significant factor influencing Pa positive culture. Patients with CF and bronchiectasis also had high Pa culture rates, an expected result as this pathogen is associated with these diseases.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our key findings are that Pa colonisation is frequent in adults on LTV, affecting nearly 1 in 5 (17.6%). Consistent with previous data [ 7 ], we found that tracheostomy is a significant factor influencing Pa positive culture. Patients with CF and bronchiectasis also had high Pa culture rates, an expected result as this pathogen is associated with these diseases.…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of Pa in the tracheostomy population was 71.7%, a higher rate than documented in previous paediatric studies [ 7 ]. Consistent with previous data [ 7 ], we also observed high rates of Pa in the cohort with cerebral palsy, but these results were not significant. This likely reflects the small sample size in this group (19).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations